2008
DOI: 10.4049/jimmunol.180.5.2903
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Is Indispensable to IL-27-Mediated Cell Proliferation but Not to IL-27-Induced Th1 Differentiation and Suppression of Proinflammatory Cytokine Production

Abstract: IL-27, a member of the IL-6/IL-12 family, activates both STAT1 and STAT3 through its receptor, which consists of WSX-1 and gp130 subunits, resulting in augmentation of Th1 differentiation and suppression of proinflammatory cytokine production. In the present study, we investigated the role of STAT3 in the IL-27-mediated immune functions. IL-27 induced phosphorylation of STAT1, -2, -3 and -5 in wild-type naive CD4+ T cells, but failed to induce that of STAT3 and STAT5 in STAT3-deficient cohorts. IL-27 induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
64
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 57 publications
4
64
0
2
Order By: Relevance
“…We, and others, previously demonstrated that IL-27 can augment the proliferation of naive CD4 ϩ T cells (1,6). Our preliminary data suggest that activation of gp130/STAT3 signaling is important for the IL-27-induced proliferation (48). In contrast, WSX-1-deficient T cells were reported to show enhanced proliferation, indicating that WSX-1 signaling has an inhibitory effect on T cell proliferation (5,49).…”
Section: Discussionmentioning
confidence: 43%
“…We, and others, previously demonstrated that IL-27 can augment the proliferation of naive CD4 ϩ T cells (1,6). Our preliminary data suggest that activation of gp130/STAT3 signaling is important for the IL-27-induced proliferation (48). In contrast, WSX-1-deficient T cells were reported to show enhanced proliferation, indicating that WSX-1 signaling has an inhibitory effect on T cell proliferation (5,49).…”
Section: Discussionmentioning
confidence: 43%
“…In human B cells, differential response to IL-27 was observed in naive and memory B cells, despite similar levels of IL-27 receptor expression (8). In mice, the differential effect of IL-27 on cytokine production in naive versus effector CD4 ϩ T cells was associated with down-regulation of gp130 and up-regulation of IL-27R␣ in effector CD4 ϩ T cells (24). Surprisingly, although IL-27R␣ is assumed to contribute preferentially to STAT1 activation and gp130 to STAT3 activation, a stronger activation of STAT3 over STAT1 was observed in effector CD4…”
Section: Discussionmentioning
confidence: 98%
“…Whereas only STAT5 was activated at higher levels in naive than memory CD4 ϩ T cells, activation of STAT1, 3 and 5 as well was more prolonged in naive than memory CD4 ϩ T cells. This sustained activation of STAT molecules, in particular that of STAT3, known to be important for IL-27-mediated proliferation (24), and possibly that of STAT5 also known to regulate T cell proliferation, may be responsible for the stronger proliferative response of naive CD4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encounters that produce longstanding cellular immunity induce a balanced cytokine milieu, using both stimulatory (STAT1) and suppressive (STAT3) signaling pathways. IL-27 is a member of the IL-12 family of cytokines and, via its signaling through both STAT1 and STAT3 (8)(9)(10)(11)(12), contributes to a spectrum of T-cell functions and phenotypes.…”
mentioning
confidence: 99%